2016
DOI: 10.1155/2016/4726267
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐Related Hypoxia Attenuates Proinflammatory Effects of Allogeneic PBMCs on Adipose‐Derived Stromal Cells In Vitro

Abstract: Human adipose tissue-stromal derived cells (ASCs) are considered a perspective tool for regenerative medicine. Depending on the application mode ASC/allogeneic immune cell interaction can occur in the systemic circulation under plenty high concentrations of O2 and in target tissues at lower O2 levels. Here we examined the effects of allogeneic PHA-stimulated peripheral blood mononuclear cells (PBMCs) on ASCs under ambient (20%) oxygen and “physiological” hypoxia (5% O2). As revealed with microarray analysis AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…When the two cells were co‐cultured, this resulted into two switches: First, that the low BMP‐2 secretion by the MSC alone was significantly enhanced, and, second, that the high TNF‐α secretion by the monocytes alone was modestly reduced. Whereas the first finding indicates a pro‐osteogenic effect for monocytes on MSC, the relative reduction of TNF‐α in the co‐culture is in line with the prevailing hypothesis of an immunosuppressive role of MSC (Bobyleva, Andreeva, Gornostaeva, & Buravkova, ; De Miguel et al, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When the two cells were co‐cultured, this resulted into two switches: First, that the low BMP‐2 secretion by the MSC alone was significantly enhanced, and, second, that the high TNF‐α secretion by the monocytes alone was modestly reduced. Whereas the first finding indicates a pro‐osteogenic effect for monocytes on MSC, the relative reduction of TNF‐α in the co‐culture is in line with the prevailing hypothesis of an immunosuppressive role of MSC (Bobyleva, Andreeva, Gornostaeva, & Buravkova, ; De Miguel et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…It has been suggested that interactions between MSC and immune cells are governed by factors in the local microenvironment (Bobyleva et al, ; Gornostaeva, Andreeva, & Buravkova, ). In the present study, no stimuli were added to mimic for instance the acute inflammation associated with the trauma induced during surgical insertion of an implant.…”
Section: Discussionmentioning
confidence: 99%
“…One such parameter is expansion of MSCs under hypoxia. A large number of studies demonstrated that MSCs cultured in hypoxia exhibit higher rates of proliferation and better retain their stem cell properties [ 25 , 30 33 ]. Yet, some studies reported conflicting results showing negative or no effects on MSCs by hypoxia [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 It is reasonable to assume that a direct cell-cell interaction leads to a more significant effect on cellular activity (due to both the close direct contacts and the effect of higher paracrine factor levels in the pericellular milieu). This change apparently includes the upregulation of matrix degradation genes and downregulation of certain extracellular matrix and regulatory molecule genes.…”
mentioning
confidence: 99%
“…This change apparently includes the upregulation of matrix degradation genes and downregulation of certain extracellular matrix and regulatory molecule genes. 16 It is reasonable to assume that a direct cell-cell interaction leads to a more significant effect on cellular activity (due to both the close direct contacts and the effect of higher paracrine factor levels in the pericellular milieu). Indeed, a number of studies demonstrated increased MSC immunosuppressive activity upon their direct contact with activated immune cells.…”
mentioning
confidence: 99%